Analysis of Motor and Cognitive Development in Early Childhood by Gender and Learning Styles Through Drawing and Coloring Activity - Isfauzi Hadi Nugroho; Anik Lestariningrum; Jamiludin Usman (Universitas Bengkulu, 2021)
Motor and cognitive development of children is very important to improve for their success in the future. This study aims to find out the development of motor and cognitive skills in early childhood by gender and learning styles through drawing and coloring activity. The subjects in this study were children aged 5-6 years consisting of 27 boys and 25 girls who attend Early Childhood Education (PAUD) in Purwoasri, Kediri Regency. This study used an experimental design. The learning styles questionnaire developed by the researcher refers to the learning style theory indicators developed by DePorter & Hernacki, (2007) which are used to identify and classify children learning styles into visual, auditory, and kinesthetic. The children's fine motor and cognitive skills were measured by assessing their ability to draw and color a picture in a worksheet. The results of the analysis using the independent T-Test sample showed that a significance value of 0,047 for drawing and 0,036 for coloring (p<0.05) in terms of gender, it means there was a difference in motor and cognitive skills used in drawing and coloring activity. The results of the One-way ANOVA analysis showed that there was no significant difference in drawing ability between the three groups of learning styles. However, a significant difference in coloring ability was found between the visual and kinesthetic groups with significance value of 0,038 (p<0,05).